2021
DOI: 10.1080/21655979.2021.1914470
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0062389 modulates papillary thyroid carcinoma progression via the miR-1179/high mobility group box 1 axis

Abstract: Circular RNAs (circRNAs) feature prominently in regulating the progression of tumors, including papillary thyroid carcinoma (PTC). This work is designated to delve into the role of circ_0062389 in PTC. Generally, quantitative real-time polymerase chain reaction (qRT-PCR) was employed to detect circ_0062389, miR-1179 and high mobility group box 1 (HMGB1) mRNA expression levels. RNase R assay was used to verify the circular characteristics of circ_0062389. After circ_0062389 was knocked down in PTC cells, CCK-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In CRC patients, HMGB1 expression is also proposed as a prognostic marker related to CRC patient survival [ 31 , 32 ]. A recent study revealed that HMGB1 is also implicated in papillary thyroid carcinoma progression [ 33 ]. However, the mechanisms regulating HMGB1 expression in CRC remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In CRC patients, HMGB1 expression is also proposed as a prognostic marker related to CRC patient survival [ 31 , 32 ]. A recent study revealed that HMGB1 is also implicated in papillary thyroid carcinoma progression [ 33 ]. However, the mechanisms regulating HMGB1 expression in CRC remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…During tumor development, HMGB1 works as both a pro-tumor and antitumor protein by facilitating or arresting tumor growth, proliferation, angiogenesis and invasion [26]. HMGB1 was confirmed to engage in the modulation of circ_0062389/miR-1179/HMGB1 axis in PTC progression as a target gene of miR-1179 [49]. As predicted in this experiment, HMGB1 was learned to be a downstream gene of miR-363-3p.…”
Section: Discussionmentioning
confidence: 75%
“…CircRNAs have been suggested to modulate downstream miRNA levels through molecular "sponge effect," thus inhibiting the malignant progression of cancer. [5][6][7][8] We have identified that miR-1294 was one the targets of circ_LDLR. Therefor, we tried to explore whether circ_LDLR promoted PTC cells by regulating miR-1294.…”
Section: Circ_ldlr Exerts Promoting Effects By Regulating Mir-1294 In...mentioning
confidence: 99%
“…Circular RNAs (circRNAs) are class of noncoding RNAs (ncRNAs) that have closed‐loop architecture, which are suggested to be the critical factors regulating carcinogenesis, including thyroid cancer. [ 5,6 ] CircRNAs can regulate a series of cellular processes involved in thyroid cancer pathogenesis, such as apoptosis, angiogenesis, tumor growth and invasion, through microRNA (miRNA) sponging action. [ 7,8 ] In PTC, many circular RNAs have been identified.…”
Section: Introductionmentioning
confidence: 99%